Steel sheet and method for manufacturing the same

CN119156281BActive Publication Date: 2026-10-23JFE STEEL CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380028546.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-03-25
Filing Date
2023-03-15
Publication Date
2026-10-23
Estimated Expiration
2043-03-15

AI Technical Summary

Technical Problem

但是,在这种情况下,有时在冲压成形后发生脱脂不良,涂装性有可能劣化

Benefits of technology

[0034]根据本发明,能够得到钢板与模具等的摩擦系数显著降低、冲压成形性优良的钢板。因此,对于要实施复杂成形的强度较低的钢板,稳定地具有优良的冲压成形性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119156281B_ABST
    Figure CN119156281B_ABST
Patent Text Reader

Abstract

The present invention provides a steel sheet to be subjected to complex forming which is difficult to be press-formed, the steel sheet being small in sliding resistance at a crack-prone portion at the time of press-forming, having excellent press-formability at a portion where surface pressure is high and sticking is expected to occur, and having good mold release property. A steel sheet including a steel sheet base and a coating film formed on at least one surface of the steel sheet base, wherein the coating film contains an organic resin and a wax, the arithmetic average roughness Ra of the steel sheet base is 0.4 μm or more, the organic resin is at least any one of an acrylic resin, an epoxy resin, a urethane resin, a phenolic resin, a vinyl acetate resin, and a polyester resin, the wax is a polyolefin wax having a melting point of 120°C or more and 140°C or less and an average particle diameter of 3.0 μm or less, the proportion of the wax in the coating film is 10% by mass or more, and the standard deviation σ of the distribution of the coating film adhesion amount per surface of the coating film is less than 0.9 g / m 2 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a steel sheet with excellent sliding properties in stamping and a method for manufacturing the same. In particular, it relates to a steel sheet with a lubricating film that exhibits excellent formability even during demanding deep drawing processes, and a method for manufacturing the same. Background Technology

[0002] Cold-rolled and hot-rolled steel sheets are widely used in a wide range of applications, primarily automotive bodies, where they are stamped for use. In recent years, there has been a demand for more integrated and sophisticated designs for parts requiring fewer manufacturing steps, necessitating the ability to perform more complex forming processes.

[0003] In cases where more complex stamping processes are required, there is a possibility that the steel sheet may not be able to withstand the forming process and break, or that sticking to the die may occur during continuous stamping, which could seriously negatively impact automobile productivity.

[0004] One method to improve the stamping formability of cold-rolled and hot-rolled steel sheets is surface treatment of the dies. While widely used, this method does not allow for die adjustments after surface treatment. Furthermore, it is costly. Therefore, there is a strong demand to improve the stamping formability of the steel sheets themselves.

[0005] One method to improve stamping formability without surface treatment of the mold is to use high-viscosity lubricating oil. However, in this case, poor degreasing sometimes occurs after stamping, and the paintability may deteriorate.

[0006] Therefore, various lubricated surface-treated steel sheets are being researched as a technology that enables stamping without the use of molds and with high-viscosity lubricating oil.

[0007] Patent document 1 describes a metal plate covered with a lubricating film that allows solid lubricant to protrude 0.01 to 1.5 μm from the surface of a resin film.

[0008] Patent document 2 describes a lubricated surface-treated metal product with excellent stamping formability, having a film of 0.5 to 5 μm thick obtained by containing lubricant in polyurethane resin.

[0009] Patent document 3 describes a technique for forming an alkali-soluble organic film on a steel plate by adding a lubricant to an epoxy resin.

[0010] Existing technical documents

[0011] Patent documents

[0012] Patent Document 1: Japanese Patent Application Publication No. 10-52881

[0013] Patent Document 2: Japanese Patent Application Publication No. 2000-309747

[0014] Patent Document 3: Japanese Patent Application Publication No. 2000-167981 Summary of the Invention

[0015] The problem that the invention aims to solve

[0016] However, in the technologies disclosed in Patent Documents 1 to 3, although lubricity is exhibited due to the lubrication effect produced by the lubricant contained therein, the stamping formability may not be sufficient in complex forming processes.

[0017] The present invention was made in view of the above circumstances, and its object is to provide a steel sheet that is difficult to stamp and form, which has low sliding resistance at the crack-prone parts during stamping and excellent stamping formability at the parts where surface pressure is high and sticking to the die is expected.

[0018] In addition, when used as steel sheet for automobiles, it is also necessary to have sufficient release properties during the alkaline degreasing process in the painting process. In such applications, a further objective is to provide steel sheets that also have good release properties.

[0019] Methods for solving problems

[0020] To address the aforementioned problems, the inventors conducted repeated and in-depth research. The results showed that, to dramatically improve stamping formability, an organic resin film containing polyolefin wax with a melting point above 120°C and below 140°C and an average particle size of less than 3.0 μm was formed on the surface of the original steel sheet, while ensuring that the standard deviation σ of the film adhesion distribution on each single side of the organic resin film was less than 0.9 g / m². 2 By controlling the surface roughness and coating adhesion distribution of the original steel sheet within a specific range, the aforementioned problems can be solved. Furthermore, it was found that by setting the coating adhesion amount, the arithmetic mean roughness Ra of the original steel sheet, the average particle size of the wax, and the proportion of wax in the coating to appropriate ranges, stamping formability can be further improved.

[0021] This invention is based on the above insights, and its main points are as follows.

[0022] It should be noted that the steel sheet base refers to the portion of the steel sheet after the coating containing organic resin and wax has been removed. Furthermore, cold-rolled steel sheet or hot-rolled steel sheet can be used as the steel sheet base.

[0023] [1] A steel plate comprising a steel plate substrate and a coating formed on at least one side of the steel plate substrate, wherein the coating comprises an organic resin and a wax, the steel plate substrate has an arithmetic mean roughness Ra of 0.4 μm or more, the organic resin is at least one of acrylic resin, epoxy resin, urethane resin, phenolic resin, vinyl acetate resin, and polyester resin, the wax is a polyolefin wax with a melting point of 120°C or higher and 140°C or lower and an average particle size of 3.0 μm or lower, the proportion of the wax in the coating is 10% by mass or more, and the standard deviation σ of the coating adhesion distribution on each side of the coating is less than 0.9 g / m 2 .

[0024] [2] According to the steel plate described in [1], wherein the coating amount W on each single side of the above-mentioned coating is 2.0 g / m 2 the following.

[0025] [3] The steel plate according to [1] or [2], wherein the arithmetic mean roughness Ra of the original steel plate is 0.4 μm or more and 2.5 μm or less.

[0026] [4] The steel plate according to any one of [1] to [3], wherein the average particle size of the wax is 0.01 μm or more and 0.5 μm or less.

[0027] [5] The steel plate according to any one of [1] to [4], wherein the proportion of the wax in the above coating is less than 50% by mass.

[0028] [6] The steel plate according to any one of [2] to [5], wherein the coating amount W on each single side of the above coating is 0.9 g / m 2 the following.

[0029] [7] The steel plate according to any one of [1] to [6], wherein the organic resin is an alkali-soluble resin.

[0030] [8] A method for manufacturing a steel plate, which is a method for manufacturing a steel plate according to any one of [1] to [7], wherein a coating containing an organic resin and a wax as described in any one of [1] to [7] is applied to at least one side of the original steel plate and dried.

[0031] [9] The steel plate manufacturing method according to [8], wherein the viscosity of the coating is 1.5 mPa·s or more and 8.0 mPa·s or less.

[0032]

[10] In the steel plate manufacturing method according to [8] or [9], the maximum temperature reached by the original steel plate during the drying process is 60°C or more and 140°C or less, and the drying time during the drying process is 2 seconds or more and 150 seconds or less.

[0033] Invention Effects

[0034] According to the present invention, it is possible to obtain a steel sheet with a significantly reduced coefficient of friction between the steel sheet and the die, etc., and excellent stamping formability. Therefore, it can stably exhibit excellent stamping formability for low-strength steel sheets that require complex forming.

[0035] Furthermore, even high-strength steel sheets with increased surface pressure during stamping can be produced with low sliding resistance in easily cracked areas during stamping and excellent stamping formability in areas with high surface pressure where sticking to the die is expected.

[0036] In addition, steel plates with good demolding properties can be obtained.

[0037] It should be noted that, in the above, high strength refers to an assumed tensile strength (TS) of 440 MPa or higher, and low strength refers to an assumed TS of less than 440 MPa. Attached Figure Description

[0038] Figure 1 This is a diagram showing the local film adhesion distribution when the difference in film adhesion between the concave and convex parts of the steel plate is different.

[0039] Figure 2 This is a graph showing the local film adhesion distribution under different average film adhesion amounts.

[0040] Figure 3 This is a diagram showing the distribution of local film adhesion under different surface roughness conditions of the original steel plate.

[0041] Figure 4 This is a schematic front view of the friction coefficient measuring device.

[0042] Figure 5 It is shown Figure 4 A rough three-dimensional drawing of the shape and dimensions of the bead in the drawing. Detailed Implementation

[0043] The embodiments of the present invention will be described below.

[0044] This invention relates to a steel plate comprising a base steel plate and a coating formed on at least one side of the base steel plate. The coating is characterized in that the coating comprises an organic resin and a wax; the arithmetic mean roughness Ra of the base steel plate is 0.4 μm or more; the organic resin is at least one of acrylic resins, epoxy resins, urethane resins, phenolic resins, vinyl acetate resins, and polyester resins; the wax is a polyolefin wax with a melting point of 120°C or higher and 140°C or lower and an average particle size of 3.0 μm or lower; and the proportion of the wax in the coating is 10% by mass or more. Furthermore, the standard deviation σ of the coating adhesion distribution on each side of the coating is less than 0.9 g / m². 2 .

[0045] The wax used in this invention is not limited to polyolefin waxes with a melting point of 120°C or higher and 140°C or lower and an average particle size of 3.0 μm or lower.

[0046] Polyolefin waxes are used because they have low surface energy and self-lubricating properties, thus providing good lubrication. Furthermore, it is relatively easy to adjust the melting point of polyolefins to be above 120°C and below 140°C by controlling their density and molecular weight.

[0047] When the melting point is above 120°C and below 140°C, in addition to the self-lubricating properties of the polyolefin wax itself, the wax becomes semi-molten due to the sliding during stamping. This allows the lubricating film component, mixed with organic resin, to coat the mold surface, achieving excellent lubrication by inhibiting direct contact between the mold and the steel plate. When the melting point is below 120°C, the wax completely melts due to the frictional heat generated during stamping, failing to provide sufficient lubrication from the wax itself or achieve the aforementioned mold coating effect. Furthermore, when the melting point is above 140°C, the wax does not melt during sliding, resulting in insufficient lubrication and mold coating.

[0048] It is believed that when the melting point of the wax is above 120°C and below 140°C, under the sliding state during stamping, the wax in the coating effectively adheres to the mold and is not easily detached, resulting in a high lubrication effect. When the melting point of the wax is below 120°C, even if the coating adheres to the mold, the adhesion is weak, and the coating is easily detached during sliding. When the melting point of the wax is above 140°C, the coating is difficult to adhere to the mold. Furthermore, the melting point of the wax is preferably above 125°C and below 135°C.

[0049] Here, the melting point of wax refers to the melting temperature determined according to JIS K 7121:1987 "Method for determination of the transformation temperature of plastics".

[0050] When the average particle size of the wax is greater than 3.0 μm, it is difficult to mix with the organic resin during sliding, making it impossible to achieve the coating effect of the mold and obtain sufficient lubrication. The average particle size of the wax is preferably 1.5 μm or less. More preferably, it is 0.5 μm or less, and even more preferably 0.3 μm or less.

[0051] The wax particle size is preferably 0.01 μm or more. When the average particle size of the wax is less than 0.01 μm, it easily dissolves in the lubricating oil during sliding, sometimes failing to provide sufficient lubrication improvement. Even in coatings used to form a film, it tends to aggregate, resulting in low coating stability. The average particle size of the wax is further preferably 0.03 μm or more.

[0052] The aforementioned average particle size refers to the median particle size of the volume average diameter, determined by laser diffraction / scattering. For example, it can be determined by measuring a sample diluted with pure water using a laser diffraction / scattering particle size distribution measuring device, Partica LA-960V2 (manufactured by Horiba Corporation).

[0053] Among polyolefin waxes, polyethylene wax is preferred because it provides the best lubrication effect.

[0054] The mass percentage of wax in the coating is set to 10% by mass or more. When the mass percentage of wax in the coating is less than 10% by mass, sufficient lubrication cannot be achieved. If the mass percentage of wax in the coating is 15% by mass or more, a particularly good lubrication effect can be obtained. Furthermore, the mass percentage of wax in the coating is preferably less than 50% by mass. When the mass percentage of wax in the coating is 50% by mass or more, due to insufficient base resin components, the wax is prone to detachment, resulting in poor adhesion to the original steel sheet, and sometimes it cannot exist stably in the coating form. In addition, when used as automotive steel sheet, sufficient degreasing is sometimes not achieved in the alkaline degreasing process during painting, and even when using alkali-soluble organic resins, sometimes insufficient degreasing occurs during the alkaline degreasing process, leaving residual coating and deteriorating coatability. The mass percentage of wax in the coating is further preferably 30% by mass or less.

[0055] Here, the proportion of wax in the coating refers to the ratio of the mass of the solid component of the wax in the coating to the total mass of the solid component of the organic resin in the coating and the solid component of the wax in the coating.

[0056] As a specific testing method, for both resin and wax, test pieces with known coating amounts on the original steel plate are prepared. Infrared absorption spectra are measured using an FT-IR measuring device, and calibration curves for the respective coating amounts of resin and wax are created based on the peak intensities from each component. Next, the infrared absorption spectrum of the lubricated coating on the steel plate is measured, and the coating amounts of resin and wax are determined from the calibration curves. From this, the mass ratio of wax in the coating can be calculated.

[0057] In this invention, the organic resin acts as an adhesive to retain the wax on the surface of the original steel plate. The sliding effect provided by the mold coating of the mixture of wax and organic resin formed during sliding cannot be achieved due to the low affinity of the inorganic adhesive for polyolefins. As the organic resin, at least one of acrylic resins, epoxy resins, urethane resins, phenolic resins, vinyl acetate resins, and polyester resins can be used.

[0058] The acrylic resins used in this invention refer to polymers or copolymers composed of one or more of the following: unsaturated monocarboxylic acids having a carboxyl group in the molecule of acrylic acid, methacrylic acid, etc.; esters of the above-mentioned unsaturated monocarboxylic acids; and styrene; or their sodium salts, potassium salts, ammonium salts, amine salts, etc.

[0059] When acrylic resins use fatty acids with two or more carboxyl groups in the molecule as monomers, the stability of the coating may deteriorate. Therefore, in this invention, acrylic resins using fatty acids or their fatty acid esters with one carboxyl group in the molecule as monomers are used.

[0060] There are no particular limitations on epoxy resins; examples include bisphenol A type epoxy resin, bisphenol F type epoxy resin, and phenolic varnish type epoxy resin.

[0061] There are no particular limitations on urethane resins, but it is preferred that they have a carboxyl group in the molecule.

[0062] There are no particular limitations on phenolic resins, but methyl phenolic resins that can be dissolved or dispersed in aqueous solvents are preferred.

[0063] There are no particular limitations on vinyl acetate resins, but polyvinyl acetate is preferred.

[0064] There are no particular limitations on polyester resins, but polyester resins containing monomers with carboxyl groups as constituent components are preferred.

[0065] In addition, two or more of these resins can be mixed. Furthermore, by using alkali-soluble organic resins, the coating film can be removed through alkaline degreasing in the coating process, resulting in good subsequent coatability.

[0066] In this invention, in addition to organic resins and waxes, surface conditioners, defoamers, and dispersants may be included as components. Additionally, rust inhibitors that improve rust resistance may also be added.

[0067] In this invention, when forming the aforementioned coating on the surface of a steel sheet, a wide range of coating amounts are formed on steel sheets with varying surface roughness, and the stamping formability is evaluated. The state of the coating is measured using SEM or EPMA equipped with an X-ray spectrometer. The results show that only on steel sheets with the aforementioned coating has the standard deviation σ of the coating adhesion distribution less than 0.9 g / m². 2 The region stably satisfies good stamping formability.

[0068] Generally, the greater the surface roughness of the steel plate, the thinner the coating becomes at the protrusions of the steel plate. During stamping, due to the sliding with the die, the coating is easily removed, exposing the steel plate as the substrate, making it difficult to achieve a lubricating effect.

[0069] However, by using the technology of the present invention, it is possible to promote the adhesion of the film component to the mold during sliding, and even when the roughness of the original steel plate is large, the mold side can be protected, thus without compromising lubricity.

[0070] In the coating, the coating component that primarily contributes to sliding properties is present on the raised parts of the original steel sheet that contact the die during stamping. Typically, because the coating coating tends to accumulate in the recessed parts of the original steel sheet during application, the coating adhesion is uneven between the raised and recessed parts, tending to be thinner on the raised parts and thicker on the recessed parts.

[0071] Furthermore, depending on the coating properties such as wettability, as well as the coating and drying conditions, even if the amount of film adhering is the same, the amount of film adhering to the protrusions of the original steel plate can sometimes be more or less.

[0072] In addition, depending on the amount of film adhesion and the roughness of the original steel plate as the substrate, the state of film adhesion on the convex part (hereinafter referred to as convex part) and the concave part (hereinafter referred to as concave part) of the original steel plate also changes.

[0073] like Figure 1 As shown, when the difference in film adhesion between the convex and concave parts increases due to variations in coating properties, coating conditions, etc., the film adhesion on the convex parts in contact with the die during stamping decreases, resulting in reduced stamping formability. In this case, the peak width of the film adhesion distribution representing the overall film thickness increases, and the standard deviation σ also increases.

[0074] In addition, such as Figure 2As shown, the peak representing the overall coating adhesion distribution changes as the average coating adhesion amount changes.

[0075] When the average film adhesion amount is low, the stamping formability decreases because the film adhesion amount of the protrusions cannot be fully obtained. In this case, the peak positions of the film adhesion amount distribution of both the protrusions and concave parts shift towards the low adhesion amount side, and the peak interval between the protrusions and concave parts widens. Consequently, the peak width of the overall film adhesion amount distribution becomes wider, and the standard deviation σ also increases.

[0076] On the other hand, when the average film adhesion amount is high, the stamping formability is improved because sufficient film adhesion amount can still be obtained from the protrusions. In this case, the peak positions of the film adhesion amount distribution for both the protrusions and concave parts shift towards the side with higher adhesion amount, and the peak interval between the protrusions and concave parts narrows. As a result, the peak width of the overall film adhesion amount distribution narrows, and the value of the standard deviation σ also decreases.

[0077] In addition, such as Figure 3 As shown, the peak width representing the overall film adhesion amount changes with variations in the roughness of the original steel plate used as the substrate. When the original steel plate roughness is low, the uneven distribution of film adhesion amount between the convex and concave portions decreases, and the film adhesion amount on the convex portions becomes more stable, thus improving stamping formability. In this case, the peak width of the film adhesion amount distribution between the convex and concave portions decreases, and the peak width of the overall film adhesion amount distribution also narrows. As a result, the value of the standard deviation σ also decreases.

[0078] Conversely, when the roughness of the original steel plate is high, the unevenness of the coating adhesion on the convex parts increases, thus reducing the stamping formability. In this case, the peak width of the coating adhesion distribution on both the convex and concave parts becomes wider. Consequently, the peak width of the overall coating adhesion distribution also becomes wider, and the value of the standard deviation σ increases.

[0079] As mentioned above, due to various reasons, the amount of film adhesion on the protrusions in contact with the mold cannot be consistently ensured, resulting in reduced stamping formability.

[0080] When the amount of film adhesion on the protrusion can be obtained stably and the stamping formability is good, the standard deviation σ of the overall film adhesion distribution becomes smaller. When the amount of film adhesion on the protrusion cannot be obtained stably and the stamping formability is poor, the standard deviation σ becomes larger.

[0081] Therefore, if the standard deviation σ of the film adhesion distribution can be evaluated, it can be determined whether the stamping formability is good.

[0082] The standard deviation σ of the above-mentioned coating adhesion distribution can be evaluated as follows: Intensity maps of C-Kα rays (the main component of the coating) and Fe-Kα rays (the main component of the original steel substrate) are measured using a SEM equipped with an X-ray spectrometer. The average value μ is calculated based on their intensity ratio maps. C / Fe and standard deviation σ C / Fe To evaluate.

[0083] Due to the average value μ C / Fe It is roughly proportional to the amount of film attached, therefore by comparing μ C / Fe The amount of film adhesion can be used to determine the standard deviation σ of the C-Kα / Fe-Kα strength ratio diagram. C / Fe Converted to the standard deviation σ of the film adhesion distribution.

[0084] Regarding the calibration curve used to convert characteristic X-ray intensity ratios into film adhesion amount, the average μ of the characteristic X-ray intensity ratio will be used. C / Fe The amount of film adhesion determined by gravimetric method when the value is 0 is set to 0, i.e., the intercept is the origin. The average μ value between the origin and the ratio of the amount of film adhesion determined by gravimetric method to the characteristic X-ray intensity is used. C / Fe The obtained points are straight lines. Furthermore, regarding the determination of the coating adhesion amount by gravimetric method, it is calculated using the change in the weight of the steel plate before and after dissolution when the organic resin-coated steel plate is impregnated in an alkaline solution with only partial dissolution of the organic resin, and the area of ​​the original steel plate with the coating formed. The average μ of the characteristic X-ray intensity ratio. C / Fe It is the standard deviation σ of the coating adhesion distribution within the same sample. C / Fe The average of all the data obtained.

[0085] When using the aforementioned characteristic X-ray images for evaluation, the accelerating voltage needs to be high enough so that even in recesses with a large amount of film adhesion, the incident electrons can reach the original steel plate serving as the substrate and generate Fe-Kα rays of sufficient intensity. Therefore, measurements can be performed at an accelerating voltage of 10 kV or higher.

[0086] However, when the accelerating voltage is too high, the generation efficiency and intensity of C-Kα rays decrease, so it is preferable to observe at a voltage below 20 kV.

[0087] Furthermore, the measurement range and analysis point size of the intensity map used in this evaluation need to be measured in a manner that is statistically significant for the unevenness of the steel plate surface. In the case of a steel plate with a surface roughness of approximately 1 μm, the diameter of the protrusion is approximately 50 μm; therefore, it is preferable to make the measurement range 200 μm × 200 μm, including at least 10 protrusions. Additionally, the analysis point size is preferably set to 10 μm or less to allow for the measurement of at least 10 points on each protrusion.

[0088] It should be noted that the measurement field of the intensity map can be measured in a manner that satisfies the above conditions, either continuously or in any two or more fields of view.

[0089] The study investigated the relationship between the standard deviation σ of the film adhesion distribution calculated above and the friction coefficient of the film measured elsewhere. The results showed that the standard deviation σ was less than 0.9 g / m². 2 The coefficient of friction becomes good.

[0090] The preferred coating thickness W per side is 2.0 g / m². 2 The following applies: The coating adhesion amount W on each single side of the film is greater than 2.0 g / m. 2 Sometimes, the film removal performance is poor. The preferred film adhesion amount W per single side is 1.5 g / m². 2 The following is particularly preferred: 0.9 g / m 2 The following applies if the coating adhesion amount W on each single side of the film is 0.9 g / m. 2 The following have particularly good desiccant properties.

[0091] The amount of film adhering can be calculated by dividing the weight difference of the steel plate before and after film coating by the area, or by completely removing the film from the steel plate with an alkaline aqueous solution or organic solvent and then dividing the weight difference of the steel plate before and after film removal by the area.

[0092] The arithmetic mean roughness Ra of the original steel plate is set to be 0.4 μm or more. Furthermore, the arithmetic mean roughness Ra of the original steel plate is preferably 2.5 μm or less.

[0093] When the arithmetic mean roughness Ra of the original steel sheet is less than 0.4 μm, the micro-damage that may occur during stamping is easily noticeable, and die biting may occur during stamping. When the arithmetic mean roughness Ra of the original steel sheet is greater than 2.5 μm, the required amount of coating material increases, manufacturing costs increase, and the clarity of the coating deteriorates.

[0094] The arithmetic mean roughness Ra (μm) of the original steel plate can be measured according to JIS B 0633:2001 (ISO 4288:1996). For example, when Ra is greater than 0.1 and less than 2, the cutoff value and reference length are set to 0.8 mm, and the evaluation length is set to 4 mm, and the roughness is determined based on the measured roughness curve. When Ra is greater than 2 and less than 10, the cutoff value and reference length are set to 2.5 mm, and the evaluation length is set to 12.5 mm, and the roughness is determined based on the measured roughness curve.

[0095] Next, the method for manufacturing the steel plate of the present invention will be described.

[0096] The method for manufacturing the steel sheet of the present invention is a method for manufacturing a steel sheet having an organic resin coating containing a polyolefin wax with a melting point of 120°C or higher and 140°C or lower and an average particle size of 3.0 μm or lower on the surface of a raw steel sheet. A coating in which the organic resin is dissolved or dispersed in a solvent, or a coating in which wax is added, is applied to the surface of the raw steel sheet and dried. Here, the coating is adjusted such that the mass (MA) of the organic resin and the mass (MB) of the wax, based on the solid components, are set to C = {MB / (MA+MB)} × 100, and C is 10% by mass or higher.

[0097] The preferred mass ratio of the coating components (organic resin and polyolefin wax) in the coating is 1% by mass or more and 25% by mass or less.

[0098] Water or organic solvents are used as solvents for coatings.

[0099] When the mass percentage of the coating component in the coating is less than 1% or greater than 25% by mass, uneven coating may sometimes occur during application. There are no particular limitations on the coating method; examples include using a roller coater, a doctor blade coater, or coating methods using spraying, dipping, or brushing. The steel sheet after coating can be dried using conventional methods. Examples include drying with hot air, drying with an IH heater, or drying with infrared heating. The maximum temperature reached during drying is preferably 60°C or higher and 140°C or lower. Below 60°C, drying is time-consuming, and sometimes rust prevention is poor. Above 140°C, the wax may melt and coalesce, resulting in coarser particle size and deteriorated lubricity; and sometimes excessive resin polymerization may occur, reducing the film-release property.

[0100] In the steel plate manufacturing method of the present invention, if the result satisfies the standard deviation σ of the film adhesion distribution being less than 0.9 g / m 2 This also enables the manufacture of steel sheets with good stamping formability.

[0101] As an example of this coating process being carried out in operation, an example with σ less than 0.9 g / m 2 Adjust the coating adhesion amount W (g / m²) on each single side of the coating by the following method. 2 The viscosity of the coating and the coating conditions. Such manufacturing conditions determination methods can be implemented as part of the steel plate manufacturing process or as a separate process.

[0102] Specifically, increasing the amount of film adhering to each side of the coating reduces the difference in film adhering amount between the convex and concave portions of the original steel plate, thereby lowering the standard deviation σ of the film adhering amount distribution. From this perspective, the preferred amount of film adhering to each side, W, is 0.3 g / m². 2 The above, especially preferred, is 0.5g / m2 That's all. However, as mentioned earlier, if the amount of film attached W is too high, the film removal performance will deteriorate. Therefore, the preferred amount of film attached W per side is 2.0 g / m². 2 The following is a preferred method for calculating the coating amount W per single side: 1.5 g / m². 2 The following is particularly preferred: 0.9 g / m 2 The following applies. Additionally, when the viscosity of the coating is too low, the coating tends to accumulate in concave areas, while the coating film thickness becomes thinner in convex areas. Sometimes, the standard deviation σ of the coating adhesion distribution becomes 0.9 g / m². 2 From this perspective, it is preferable to set the viscosity of the coating to 1.5 mPa·s or higher. On the other hand, if the viscosity of the coating is too high, uneven coating application can easily occur, and sometimes streaks or other defects may appear after the film has formed, resulting in a poor appearance. Therefore, it is preferable to set the viscosity of the coating to 8.0 mPa·s or lower.

[0103] Furthermore, when the drying time of the coating increases, the coating wets and spreads during the period before drying, and the coating tends to accumulate in the concave areas, while the liquid film thickness of the coating in the convex areas becomes thinner, sometimes resulting in a film area ratio of 25% or more. Therefore, by increasing the drying temperature as much as possible and shortening the drying time within the range that satisfies the target characteristics of the coating, it is possible to reduce the film area ratio of the coating to 25% or less. As for the drying temperature, 60°C or higher is preferred, and 80°C or higher is particularly preferred. On the other hand, as mentioned above, when the drying temperature is higher than 140°C, the wax may melt and coalesce, resulting in coarsening of the particle size and deterioration of lubricity. Therefore, the drying temperature is preferably 140°C or lower. In addition, as for the drying time, 150 seconds or less is preferred, 120 seconds or less is more preferred, and 60 seconds or less is particularly preferred. However, if the drying time is too short, the coating cannot dry sufficiently, and sometimes the corrosion resistance decreases. Therefore, the drying time is preferably 2 seconds or more, and particularly preferably 4 seconds or more.

[0104] As described above, by appropriately controlling the amount of film adhering to each side of the coating, the viscosity of the coating, and the drying time of the coating, the standard deviation σ of the film adhesion distribution can be made less than 0.9 g / m. 2 .

[0105] Example

[0106] The present invention will now be described through embodiments. It should be noted that the present invention is not limited to the following embodiments.

[0107] Using cold-rolled steel sheets (sheet No. A to C) with a thickness of 0.8 mm and an arithmetic mean roughness Ra as shown in Table 1, and hot-rolled steel sheets (sheet No. D, E, and F) with a thickness of 2.0 mm as the base sheets, a coating with the composition shown in Table 2 was applied using a doctor blade coater. The sheets were then dried using an IH heater at a maximum temperature of 80°C, thereby obtaining steel sheets with a film containing organic resin and wax. It should be noted that the base sheets A to F are all SPCD or SPHD with a tensile strength of 270 MPa.

[0108]

[0109]

[0110] (1) Evaluation method of stamping formability (sliding characteristics)

[0111] To evaluate the stamping formability of the obtained steel sheet, the coefficient of friction of the steel sheet was measured as follows.

[0112] Figure 4 This is a schematic front view of the friction coefficient measuring device. As shown in the figure, a friction coefficient measuring sample 1, cut from the obtained steel plate, is fixed on a sample stage 2, and the sample stage 2 is fixed on the upper surface of a horizontally movable slide 3. A slide support 5, having a roller 4 in contact with the lower surface, is provided on the lower surface of the slide 3 and is movable vertically. A first force sensor 7 is mounted on the slide support 5, and this first force sensor 7 is used to measure the pressing load N of the pressure rib 6 on the friction coefficient measuring sample 1 due to pushing the slide support 5 upward. A second force sensor 8 is mounted on one end of the slide 3, and this second force sensor 8 is used to measure the sliding resistance F that causes the slide 3 to move horizontally under the aforementioned pressing force. It should be noted that Preton (registered trademark) R352L, a stamping cleaning oil manufactured by Sugimura Chemical Industry Co., Ltd., is applied to the surface of the sample 1 for testing.

[0113] Figure 5 This is a schematic perspective view showing the shape and dimensions of the blank holder used. The blank holder 6 is slid in a position where its lower surface is pressed against the surface of the sample 1. Regarding... Figure 5 The shape of the pressing rib 6 shown is 10 mm wide and 59 mm long in the sliding direction of the sample. The lower part of both ends in the sliding direction is composed of a curved surface with a curvature of 4.5 mmR. The lower surface of the pressing rib pressing the sample has a plane with a width of 10 mm and a sliding direction length of 50 mm.

[0114] Regarding the friction coefficient determination test, the following is used: Figure 5The pressure bar shown was tested with a pressure load N set to 400 kgf and a sample pull-out speed (horizontal movement speed of slide 3) set to 20 cm / min. The coefficient of friction μ between the test material and the pressure bar was calculated using the formula: μ = F / N.

[0115] A friction coefficient below 0.119 is considered to have excellent sliding performance and is rated ◎. A friction coefficient between 0.119 and 0.130 is considered to have good sliding performance and is rated ○. A friction coefficient above 0.130 is considered to have insufficient sliding performance and is rated ×.

[0116] (2) Evaluation method of desiccation property

[0117] Imagine using the steel sheet of the present invention for automotive applications, and evaluate the degreasing properties of the steel sheet during degreasing. To determine the degreasing properties of the steel sheet, firstly, test pieces cut from the obtained steel sheet were degreased using Fine Cleaner (registered trademark) E6403 (manufactured by Pakase Sei Co., Ltd., Japan), an alkaline degreasing agent. For this treatment, the test pieces were immersed in a degreasing solution with a degreasing agent concentration of 20 g / L and a temperature of 40°C for a specified time, and then rinsed with tap water. For the treated test pieces, the surface carbon strength was measured using a fluorescence X-ray analysis device. Using this measured value, along with the pre-measured surface carbon strength before degreasing and the measured surface carbon strength of the untreated steel sheet, the film peeling rate was calculated according to the following formula.

[0118] Coating peel rate (%) = [(Carbon strength before degreasing - Carbon strength after degreasing) / (Carbon strength before degreasing - Carbon strength of untreated steel plate)] × 100

[0119] Regarding the peelability of the steel plate, it is evaluated according to the following criteria based on the immersion time in an alkaline degreasing solution with a peel rate of 98% or higher. Under the conditions ◎, 〇, or △ below, the peelability is deemed acceptable.

[0120] ◎(Exceptionally Good): Within 15 seconds

[0121] ○ (Good): Greater than 15 seconds and less than 45 seconds

[0122] △ (Pass): Greater than 45 seconds and less than 120 seconds

[0123] × (Poor): More than 120 seconds

[0124] (3) Evaluation method of standard deviation σ of film adhesion amount

[0125] The standard deviation σ of the coating adhesion amount of the obtained steel plate was determined in the following manner.

[0126] Five 10mm square pieces were cut from the steel plate obtained above as test materials. In the measurements, a Schottky field emission SEM (Carl Zeiss Σigma) equipped with an energy-dispersive X-ray spectroscopy device (Bruker XFlash5|30) was used.

[0127] For each level of steel plate, intensity maps of C-Kα and Fe-Kα rays were measured near the center of each of the five test materials at a magnification of 300x, under an accelerating voltage of 15kV and a measurement point count of 800 × 600 points. The measured C-Kα ray intensity map was divided by the corresponding Fe-Kα ray intensity map to calculate the C-Kα / Fe-Kα intensity ratio. Furthermore, the average value μ of the C-Kα / Fe-Kα intensity ratio was determined from the intensity ratio map. C / Fe and standard deviation σ C / Fe The average value of the five fields of view is used for evaluation. Furthermore, the average value μ is used for... C / Fe The relationship with the amount of film adhesion is expressed as the standard deviation σ of the C-Kα / Fe-Kα strength ratio. C / Fe This is converted to the standard deviation σ of the film adhesion amount. The σ calculated above is less than 0.9 g / m³. 2 The condition was rated as good (○) under the condition that σ was 0.9 g / m 2 In the above cases, the evaluation is poor (×).

[0128]

[0129]

[0130]

[0131] According to Tables 3-5, the steel sheets of the present invention all exhibit excellent stamping formability. In contrast, the steel sheets of the comparative examples, which do not possess the technical features of the present invention, all have poor stamping formability. Furthermore, by setting the mass ratio of wax in the film to less than 50% by mass and setting the adhesion amount of the film per single side to 2.0 g / m... 2 The following results showed excellent delamination properties.

[0132] Industrial availability

[0133] The steel sheet of the present invention has excellent stamping formability and release properties, and therefore can be applied to a wide range of fields, primarily automobile body applications.

[0134] Symbol Explanation

[0135] 1. Sample for friction coefficient determination

[0136] 2 Sample Stage

[0137] 3 slides

[0138] 4 rollers

[0139] 5 slide support platform

[0140] 6 edge reinforcement bars

[0141] 7 First force sensor

[0142] 8. Second force sensor

[0143] 9 guide rails

Claims

1. A steel plate comprising a steel plate substrate and a coating formed on at least one side of the steel plate substrate, wherein, The coating contains organic resin and wax. The arithmetic mean roughness Ra of the original steel plate is above 0.4 μm. The organic resin is at least one of acrylic resins, epoxy resins, carbamate resins, phenolic resins, vinyl acetate resins, and polyester resins. The wax is a polyolefin wax with a melting point above 120°C and below 140°C and an average particle size of less than 3.0 μm. The proportion of wax in the coating is 10% by mass or more. The standard deviation σ of the film adhesion distribution on each single side of the film is less than 0.9 g / m. 2 , The arithmetic mean roughness Ra was measured according to JIS B 0633:2001. The standard deviation σ of the coating adhesion distribution is evaluated as follows: For each level of steel plate, intensity maps of C-Kα and Fe-Kα rays at a magnification of 300x are measured near the center of each of the five test materials, under the conditions of an accelerating voltage of 15kV and a measurement point count of 800 points × 600 points. The average value μ of the C-Kα / Fe-Kα intensity ratio is obtained from the calculated C-Kα / Fe-Kα intensity ratio map. C / Fe and standard deviation σ C / Fe , by average value μ C / Fe The relationship with the amount of film adhesion is expressed as the standard deviation σ of the C-Kα / Fe-Kα strength ratio. C / Fe Converted to the standard deviation σ of the film adhesion distribution.

2. The steel plate according to claim 1, wherein, The coating adhesion amount W on each single side of the coating is 2.0 g / m. 2 the following.

3. The steel plate according to claim 1, wherein, The arithmetic mean roughness Ra of the original steel plate is above 0.4 μm and below 2.5 μm.

4. The steel plate according to claim 2, wherein, The arithmetic mean roughness Ra of the original steel plate is above 0.4 μm and below 2.5 μm.

5. The steel plate according to claim 1, wherein, The wax has an average particle size of 0.01 μm or more and 0.5 μm or less.

6. The steel plate according to claim 2, wherein, The wax has an average particle size of 0.01 μm or more and 0.5 μm or less.

7. The steel plate according to claim 3, wherein, The wax has an average particle size of 0.01 μm or more and 0.5 μm or less.

8. The steel plate according to claim 4, wherein, The wax has an average particle size of 0.01 μm or more and 0.5 μm or less.

9. The steel plate according to claim 1, wherein, The proportion of wax in the coating is less than 50% by mass.

10. The steel plate according to claim 2, wherein, The proportion of wax in the coating is less than 50% by mass.

11. The steel plate according to claim 3, wherein, The proportion of wax in the coating is less than 50% by mass.

12. The steel plate according to claim 5, wherein, The proportion of wax in the coating is less than 50% by mass.

13. The steel plate according to claim 6, wherein, The proportion of wax in the coating is less than 50% by mass.

14. The steel plate according to claim 7, wherein, The proportion of wax in the coating is less than 50% by mass.

15. The steel plate according to claim 2, wherein, The coating adhesion amount W on each single side of the coating is 0.9 g / m. 2 the following.

16. The steel plate according to claim 1, wherein, The organic resin is an alkali-soluble resin.

17. A method for manufacturing a steel plate, wherein the method for manufacturing a steel plate is as described in any one of claims 1 to 16, wherein, A coating containing the organic resin and wax described in any one of claims 1 to 16 is applied to at least one side of the original steel plate and dried.

18. The method for manufacturing a steel plate according to claim 17, wherein, The viscosity of the coating is above 1.5 mPa·s and below 8.0 mPa·s.

19. The method for manufacturing a steel plate according to claim 17, wherein, The maximum temperature reached by the original steel plate during drying is above 60°C and below 140°C, and the drying time is above 2 seconds and below 150 seconds.

20. The method for manufacturing a steel plate according to claim 18, wherein, The maximum temperature reached by the original steel plate during drying is above 60°C and below 140°C, and the drying time is above 2 seconds and below 150 seconds.

Citation Information

Patent Citations

  • Resin coated metal plate with mold drag resistance and corrosion resistance and its manufacture

    JP1998052881A

  • Alkali-soluble type organic film-coated steel sheet having excellent adhesiveness and anti-mold galling property

    JP2000167981A

  • Coating composition having ability to form lubricative film excellent in press-moldability and scuffing- resistance, and of alkali-soluble type, and metal product having lubricatively treated surface using this composition

    JP2000309747A

  • Steel sheet having lubricating film and production method therefor

    CN112513330A

  • Non-alkali decorating type lubricating resin treated steel plate and manufacture thereof

    JP1998109376A